SHOLAT SEBAGAI SARANA PELATIHAN MINDFULNESS: JAWABAN UNTUK TANTANGAN PENDIDIKAN ISLAM MENGHADAPI THEAGE OF COMPLEXITY - Victor Imaduddin Ahmad; Ahmad Suyuthi (Universitas Islam Lamongan, 2019)
The purpose of this paper is to answer the questions of what is the potential of prayer as a medium for mindfulness training and how is its implementation to face the age of complexity. The results of the study concludes that prayer has aspects that are complete enough to fulfill the components of mindfulness with an Islamic mindset, in which the object of focus is God. Based on the Quran and al Hadith it was found that solemn or mindful prayer has a great influence on the quality of life of a Muslim. This is in line with the results of research on mindfulness which shows that the increased mindfulness will improve mental quality and body health and well-being. To get quality prayer, one needs to do five things. (1) Starting with the so-called taawudz (2) Strengthening the intention of prayer to achieve the ridha of Allah. (3) Performing every prayer move with tuma'ninah. (4) grasping every prayer reading and presenting muraqabah. (5) Making prayers as needed. Transforming the mindful prayer into all aspects of life requires three keys, namely deep breathing, positive feelings, and involving mindful prayer to the areas of life by forming the mindset of a